Accession of Tumor Heterogeneity by Multiplex Transcriptome Profiling of Single Circulating Tumor Cells. (6th January 2020) - Gorges, Tobias M; Kuske, Andra; Röck, Katharina; Mauermann, Oliver; Müller, Volkmar; Peine, Sven; Verpoort, Karl; Novosadova, Vendula; Kubista, Mikael; Riethdorf, Sabine; Pantel, Klaus
Abstract: BACKGROUND: Transcriptome analysis of circulating tumor cells (CTCs) holds great promise to unravel the biology of cancer cell dissemination and identify expressed genes and signaling pathways relevant to therapeutic interventions. METHODS: CTCs were enriched based on their EpCAM expression (CellSearch ® ) or by size and deformability (Parsortix TM ), identified by EpCAM and/or pan-keratin–specific antibodies, and isolated for single cell multiplex RNA profiling. RESULTS: Distinct breast and prostate CTC expression signatures could be discriminated from RNA profiles of leukocytes. Some CTCs positive for epithelial transcripts ( EpCAM and KRT19 ) also coexpressed leukocyte/mesenchymal associated markers ( PTPRC and VIM ). Additional subsets of CTCs within individual patients were characterized by divergent expression of genes involved in epithelial–mesenchymal transition (e.g., CDH2, MMPs, VIM, or ZEB1 and 2 ), DNA repair ( RAD51 ), resistance to cancer therapy (e.g., AR, AR-V7, ERBB2, EGFR ), cancer stemness (e.g., CD24 and CD44 ), activated signaling pathways involved in tumor progression (e.g., PIK3CA and MTOR ) or cross talks between tumors and immune cells (e.g., CCL4, CXCL2, CXCL9, IL15, IL1B, or IL8 ). CONCLUSIONS: Multimarker RNA profiling of single CTCs reveals distinct CTC subsets and provides important insights into gene regulatory networks relevant for cancer progression and therapy.